Pengaruh Kesabaran terhadap Stres Akademik pada Mahasiswa Tingkat Akhir di Kota Bandung - Zahra Qolbina; Yusuf, Umar (UNISBA Press, 2024)
Abstract. Academic demands on final-semester students can lead to a psychological condition known as academic stress, especially when writing a thesis. To address this, mental strength, specifically patience, is required. This research aimed to determine the extent of the influence of patience on academic stress among students in Bandung City. This study used a quantitative approach using accidental sampling as the research method, with 168 respondents tested using multiple regression analysis. The measurement tool used for the patience variable was based on Umar Yusuf's (2020) instrument, referencing Umar Yusuf's (2020) patience theory, with a validity score above 0.3 and a reliability score of 0.93. The assessment tool used for the academic stress variable was based on Wulandari's (2014) instrument, referencing Sarafino's (2011) stress theory, with item validity scores above 0.3 and a reliability score of 0.92. The results of the multiple regression analysis indicate a significant influence of patience on academic stress, with a substantial contribution of patience at 0.67 to academic stress. The aspect of resilience is identified as the dominant factor influencing academic stress. Abstrak. Tuntutan akademik pada mahasiswa semester akhir dapat menyebabkan suatu kondisi psikologis yang dinamakan stres akademik, tertutama selama proses penyusunan skripsi. Untuk mengatasi kondisi tersebut, dibutuhkan kekuatan mental yaitu kesabaran. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh kesabaran terhadap stres akademik pada Mahasiswa di Kota Bandung. Penelitian ini menggunakan pendekatan kuantitatif dengan metode penelitian menggunakan accidental sampling dan mendapatkan 168 responden yang di uji menggunakan uji analisis regresi berganda. Alat ukur yang digunakan pada variabel kesabaran ialah alat ukur milik Umar Yusuf (2020) yang mengacu pada teori kesabaran Umar Yusuf (2020) dengan nilai validitas diatas 0.3 dan nilai reliabilitas 0.93 dan pada variabel stres akademik menggunakan alat ukur Wulandari (2014) yang mengacu pada teori Sarafino (2011) dengan nilai validitas item diatas 0.3 dan nilai reliabilitas 0.92. Hasil uji regresi berganda menyatakan terdapat pengaruh signifikan kesabaran terhadap stres akademik dengan besar pengaruh sumbangan kesabaran sebesar 0.67 terhadap stres akademik. Dan aspek teguh yang menjadi aspek dominan yang mempengaruhi stres akademik.